1973
DOI: 10.1113/jphysiol.1973.sp010381
|View full text |Cite
|
Sign up to set email alerts
|

Receptive field organization of bipolar and amacrine cells in the goldfish retina

Abstract: SUMMARY1. Intracellular recordings were made from bipolar and amacrine cells in the isolated goldfish retina. Cells were identified mainly from their response patterns to a spot and an annulus in reference to the knowledge obtained from the previous work of intracellular Procion Yellow injection. Using white light and monochromatic lights receptive field organization of recorded cells were analysed.2. All bipolar cells had a centre-surround organization in their receptive fields. The field centre was estimated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
138
0

Year Published

1975
1975
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(145 citation statements)
references
References 20 publications
(50 reference statements)
7
138
0
Order By: Relevance
“…Receptive fields were computed by the standard method of reverse correlating the activity of model units with a white noise input. We found that the receptive fields of CNN units had the well-known structure of retinal interneurons 20,21 , with a spatially localized center-surround structure ( Fig. 2A-B, Extended Data, Fig.…”
Section: Cnn Internal Units Have Receptive Field Structure Matching Rmentioning
confidence: 84%
“…Receptive fields were computed by the standard method of reverse correlating the activity of model units with a white noise input. We found that the receptive fields of CNN units had the well-known structure of retinal interneurons 20,21 , with a spatially localized center-surround structure ( Fig. 2A-B, Extended Data, Fig.…”
Section: Cnn Internal Units Have Receptive Field Structure Matching Rmentioning
confidence: 84%
“…Retinal bipolar cells respond to light stimulation with graded potentials (Werblin and Dowling, 1969;Kaneko, 1973). However, recent studies have shown that bipolar cells have the ability to generate Ca (2003)].…”
Section: Spread Of Ca 2؉ Spikes Through Gap Junctionsmentioning
confidence: 99%
“…Although existence of gap junctions between BCs was reported more than two decades ago (Kujiraoka and Saito, 1986), their properties and functional roles have not yet been elucidated. It is generally accepted that retinal BCs respond to light stimulation with graded potentials (Werblin and Dowling, 1969;Kaneko, 1973). However, recent studies show that some types of BCs have the ability to generate Ca 2ϩ and/or Na ϩ spikes [Ca 2ϩ spikes: Burrone and Lagnado (1997), Zenisek and Matthews (1998), Protti et al (2000), Hull et al (2006), Palmer (2006), and Hu et al (2009); Na ϩ spikes: Ma et al (2005); Ca 2ϩ and Na ϩ spikes: Ma and Pan (2003)].…”
Section: Introductionmentioning
confidence: 99%
“…These two inputs usually affect the bipolars in opposite ways. A bipolar cell, which hyperpolarizes when stimulated directly by receptors, will depolarize when driven indirectly by horizontal cells, and vice versa (Werblin & Dowling, 1969;Kaneko, 1970Kaneko, , 1973Werblin, 1974). These opposite bipolar responses seem to produce the antagonistic on-off responses of simply organized ganglion cells (Werblin & Dowling, 1969;Kaneko, 1973).…”
Section: Discussionmentioning
confidence: 99%
“…A bipolar cell, which hyperpolarizes when stimulated directly by receptors, will depolarize when driven indirectly by horizontal cells, and vice versa (Werblin & Dowling, 1969;Kaneko, 1970Kaneko, , 1973Werblin, 1974). These opposite bipolar responses seem to produce the antagonistic on-off responses of simply organized ganglion cells (Werblin & Dowling, 1969;Kaneko, 1973). The class 4 cells in the frog retina, which receive on signals RECEPTIVE FIELDS OF FROG GANGLION CELLS 101 with long latency from the green rods and off signals from the cones (Reuter & Virtanen, 1972), behave as if they were driven by bipolars receiving direct inputs from cones and horizontal cell-mediated signals from the green rods.…”
Section: Discussionmentioning
confidence: 99%